Next-Generation Sequencing Reveals the Potential Role of RET Protooncogene in Metastasis Progression in Medullary Thyroid Cancer - Maurice Klein; Anna Julia Claudia Klein; Arnold M. Raem; Nicklas Garrelfs; Henrike J. Fischer; Frank Hölzle; Kai Wermker (Current Issues in Molecular Biology, 2025)
Background: Medullary thyroid carcinoma (MTC) has a high rate of local and distant metastases. In particular, the RET protooncogene appears to be the predominant driver mutation for oncogenesis. The German S3 thyroid carcinoma guidelines recommend molecular genetic analysis of the tumour without specifying the site of the tissue sampling. Whether there is difference in RET protooncogene between the primary tumour, lymph node, and distant metastasis has not yet been investigated. However, differences could be important with regard to biopsy localization, and also, thus, the choice of single- or multi-tyrosine-kinase-inhibitor therapy. Methods: In a case of sporadic MTC, Cancer Hotspot panel diagnostics were performed on the primary tumour, lymph node metastasis, and distant metastasis. Mutations were classified using different gene databases, and the different stages of metastasis were compared. Results: RET protooncogene (chr10:43609933, c.1886_1891delTGTGCG, p.Leu629_Asp631delinsHis) was found to be present in the MTC tissue of the primary tumour, lymph node, and distant metastasis in the Cancer Hotspot Panel diagnostic, while the other investigated therapy-relevant mutational profiles were not consistently found. Conclusions: Further longitudinal studies in larger patient cohorts are required to elucidate the role of the RET protooncogene in the metastatic progression of MTC and to determine its impact on the selection of biopsy sites and the subsequent decision-making regarding single- versus multi-tyrosine kinase inhibitor therapy.